Advances in Studies on Functional Components and Pharmacological Effects of Dioscorea opposita Thunb - Jingzhi PAN; Qinglong MENG; Wenyu CUI; Shuangjie ZHU (Shipin gongye ke-ji, 2023)
Dioscorea opposita Thunb, as homologous plant of traditional medicine and food in our country, is the important raw material for healthy food. D. opposita maily contains variety of functional components such as polysaccharides, saponins, polyphenols, proteins, and trace elements. Many researchers have confirmed that D. opposita has the effects of immune regulation, anti-tumor, anti-oxidation, anti-aging, lowering blood sugar, lowering blood lipids, and regulating the spleen and stomach. Consequently, D. opposita has good development potential and application prospects in the fields of medicine, health and food products. Recently, the extraction, separation and pharmacological effects of functional components from D. opposita have been drawing much attention from scholars around the world. However, different species, different extraction and separation methods affect the structure and efficacy of functional components. This paper systematically reviews the functional components and the hottest pharmacological effects of D. opposita to broaden the application scope of D. opposita in many fields and industries, and analyze the relationship between functional components and efficacy, to provide a reference for the development and utilization of D. opposita functional food and health medicine.